Influence of Foreign Ownership, Ownership Concentrated, and Environmental Disclosure to Firm Value - Elfira Roza Fitri; Enni Savitri; Al Azhar L (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This study aims to examine the effect of foreign ownership on firm value, the influence of ownership concentrated on firm value, the influence of the environmental disclosure on firm value. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2014-2017. Samples were determined by using purposive sampling method and obtained sample of 13 companies with a total of 134 observations. Data analysis was done by multiple regression analysis using SPSS program. The results of the research indicate that: 1) foreign ownership influences on firm value, 2) ownership concentrated influences on firm value, 3) environmental disclosure influences on firm value.